Ethical conflicts associated with COVID-19 pandemic, triage and frailty-unexpected positive disease progression in a 90-year-old patient: A case report. - Wehrfritz, Andreas; Schmidt, Joachim; Bremer, Frank Felix; Lang, Anne-Katharina; Welzer, Jacob; Castellanos, Alvaro Ixchel (Clinical Case Reports, 2023)
During the COVID 19 pandemic, advanced age, scoring systems, and a shortage of ICU beds were used as cut-offs for ICU admission. This case report describes the epicrisis of an elderly patient who was almost mistakenly not treated in an ICU.
EVALuna2:547214

Key characteristics impacting survival of COVID-19 extracorporeal membrane oxygenation - Herrmann, Johannes; Lotz, Christopher; Karagiannidis, Christian; Weber-Carstens, Steffen; Kluge, Stefan; Putensen, Christian; Wehrfritz, Andreas; Schmidt, Karsten; Ellerkmann, Richard K.; Oswald, Daniel; Lotz, Gosta; Zotzmann, Viviane; et al. (Critical Care, 2022)
Background: Severe COVID-19 induced acute respiratory distress syndrome (ARDS) often requires extracorporeal membrane oxygenation (ECMO). Recent German health insurance data revealed low ICU survival rates. Patient characteristics and experience of the ECMO center may determine intensive care unit (ICU) survival. The current study aimed to identify factors affecting ICU survival of COVID-19 ECMO patients.
CRIS-Team WoS Importer:2022-07-08

Long-Term Stability of Hydromorphone in Human Plasma Frozen at-20 degrees C for Three Years Quantified by LC-MS/MS - Wehrfritz, Andreas; Schmidt, Stefanie; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (International Journal of Analytical Chemistry, 2022)
The long-term stability of drugs under normal laboratory storage conditions (-20 degrees C) for years is important for research purposes, clinical re-evaluation, and also for forensic toxicology. To evaluate the stability of the analgesic opioid hydromorphone, 44 human frozen plasma samples of a former clinical trial were reanalyzed after at least three years. Blood samples were disposed using solid-phase extraction with an additional substitution of stable isotope labelled hydromorphone as an internal standard. Hydromorphone concentrations were determined by ultra-performance liquid chromatography (UPLC) with gradient elution, followed by tandem mass spectrometry with electrospray ionization. Calibration curves demonstrated linearity of the assay in the concentration range of 0.3-20 ng/mL hydromorphone. The limit of detection of the hydromorphone plasma concentration was 0.001 ng/mL, and the lower limit of quantification was 0.3 ng/mL. Intra- and interassay errors did not exceed 16%. The percentage deviation of the measured hydromorphone plasma concentrations between the reanalysis and the first analysis was -1.07% +/- 14.8% (mean +/- SD). These results demonstrate that hydromorphone concentration in human plasma was stable when the samples were frozen at -20 degrees C over three years. This finding is of value for re-evaluations or delayed analyses for research purposes and in pharmacokinetic studies, such as in forensic medicine.
CRIS-Team WoS Importer:2022-07-29

Long-term stability of sufentanil quantified by UPLC-MS-MS in human plasma frozen for 11 years at -20°C. - Wehrfritz, Andreas; Schmidt, Stefanie; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (Journal of Analytical Toxicology, 2025)
The long-term stability of drug concentrations in human plasma samples, when stored under normal laboratory conditions over several years, is important for research purposes and clinical re-evaluation, and forensic toxicology. Fifty human plasma samples from a former clinical trial were re-analyzed after storage at -20°C for 11 years. Plasma samples were extracted using solid-phase extraction. Isotope labeled sufentanil-d5 was used as internal standard. Sufentanil plasma concentrations were determined by ultra-performance liquid chromatography with gradient elution, followed by tandem mass spectrometry with electrospray ionization. The linear dynamic range was 25-2500 pg/mL, the limit of detection was 10 pg/mL, and the lower limit of quantification was 25 pg/mL. Intra- and inter-assay error did not exceed 6%. The deviation of the measured sufentanil plasma concentrations between the re-analysis and the first analysis was -63 ± 14% (mean ± SD). Therefore, sufentanil concentrations in human plasma were not stable in samples frozen at -20°C over 11 years.
EVALuna2:582596

Patient-Controlled Analgesia After Cardiac Surgery With Median Sternotomy: No Advantages of Hydromorphone When Compared to Morphine - Wehrfritz, Andreas; Senger, Anne-Sophie; Just, Patrick; Albart, Maximilian; Münchsmeier, Michael; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (Journal of Cardiothoracic and Vascular Anesthesia, 2022)
Objectives: To compare the efficacy, safety, and side effects of hydromorphone and morphine administered as patient-controlled analgesia (PCA) for postoperative pain therapy after cardiac surgery with median sternotomy. Design: A retrospective analysis of data from 2 prospective, single-blinded, randomized trials. Setting: A single-center intensive care unit at a university hospital. Participants: Forty-one adult patients undergoing cardiac surgery with median sternotomy. Interventions: Postoperative pain therapy at the intensive care unit was performed by PCA with intravenously administered bolus doses of 0.2 mg of hydromorphone (n = 21) or 2 mg of morphine (n = 20). Measurements and Main Results: Pain at rest and under deep inspiration regularly was assessed using the 11-point numerical rating scale (NRS). Blood pressure, heart rate, cardiac output, oxygen saturation, and respiratory rate were monitored, and adverse events were registered. The median (range) NRS rating at rest was 1.5 (0-5) after hydromorphone and 0.5 (0-5) after morphine, respectively (p = 0.41). The median NRS rating under deep inspiration was 3 (0-6) after hydromorphone and 4 (0-7) after morphine, respectively (p = 0.074). The dose ratio of morphine to hydromorphone during PCA was 5.7 (95% confidence interval: 2.9-7.6). Hemodynamics and respiration were stable and did not differ significantly. Postoperative nausea and vomiting were the most frequent adverse events, which were observed in 29% of the patients after hydromorphone and in 35% after morphine, respectively (p = 0.74). Conclusions: There were no significant differences in analgesic efficacy and safety between hydromorphone and morphine when used for postoperative pain therapy with PCA after cardiac surgery with median sternotomy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: adverse events; hydromorphone; morphine; NRS pain rating; Patient-controlled analgesia

Streptococcal toxic shock syndrome with associated necrotising fasciitis necessitating amputation of the lower extremity – A case report - Strecker, Thomas; Treutlein, Christoph; Agaimy, Abbas; Wehrfritz, Andreas (SAGE Open Medical Case Reports, 2023)
Streptococcal toxic shock syndrome is a severe, invasive and life-threatening infection associated with a high risk of rapid multiorgan failure. It is associated with high morbidity and mortality. Streptococcal toxic shock syndrome is very commonly caused by group A-Streptococcus pyogenes, ß-haemolytic streptococcus, a typical human-specific gram-positive bacterial pathogen. We present here the case report of a 54-year-old man with a rapidly progressive streptococcal toxic shock syndrome due to necrotising fasciitis of the left lower limb and describe the successful treatment through close interdisciplinary care.
CRIS-Team Scopus Importer:2023-10-27
Keywords: amputation; computer tomography; group A-Streptococcus pyogenes; necrotising fasciitis; Streptococcal toxic shock syndrome; β-haemolytic streptococcus